Uncommon structural motifs dominate the antigen binding site in human autoantibodies reactive with basement membrane collagen. (August 2016) - Foster, Mary H.; Buckley, Elizabeth S.; Chen, Benny J.; Hwang, Kwan-Ki; Clark, Amy G.
Highlights: We report isolation of human monoclonal antibodies (mAb) reactive with alpha3(IV)NC1 collagen from humanized Hu-HSC mice. The mAb antigen binding sites are dominated by exceptionally long heavy chain complementarity determining region3s (HCDR3s). Long HCDR3 are also found in polyreactive bnAb and can bind to recessed epitopes immunologically silent to conventional Ig. B cells with long HCDR3 are normally negatively selected and may require transient escape from tolerance or expansion. The mAb also use unmutated Ig genes enriched in chronic lymphocytic leukemia Ig with features of natural polyreactive Ig. Abstract: Autoantibodies mediate organ destruction in multiple autoimmune diseases, yet their origins in patients remain poorly understood. To probe the genetic origins and structure of disease-associated autoantibodies, we engrafted immunodeficient mice with human CD34+ hematopoietic stem cells and immunized with the non-collagenous-1 (NC1) domain of the alpha3 chain of type IV collagen. This antigen is expressed in lungs and kidneys and is targeted by autoantibodies in anti-glomerular basement membrane (GBM) nephritis and Goodpasture syndrome (GPS), prototypic human organ-specific autoimmune diseases. Using Epstein Barr virus transformation and cell fusion, six human anti-alpha3(IV)NC1 collagen monoclonal autoantibodies (mAb) were recovered, including subsets reactive with human kidney and with epitopes recognized by patients' IgG. Sequence analysis reveals a long to exceptionally long heavy chain complementarity determining region3 (HCDR3), the major site of antigen binding, in all six mAb. Mean HCDR3 length is 25.5 amino acids (range 20–36), generated from inherently long DH and JH genes and extended regions of non-templated N-nucleotides. Long HCDR3 are suited to forming noncontiguous antigen contacts and to binding recessed, immunologically silent epitopes hidden from conventional antibodies, as seen with self-antigen crossreactive broadly neutralizing anti-HIV Ig (bnAb). The anti-alpha3(IV)NC1 collagen mAb also show preferential use of unmutated variable region genes that are enriched among human chronic lymphocytic leukemia antibodies that share features with natural polyreactive Ig. Our findings suggest unexpected relationships between pathogenic anti-collagen Ig, bnAb, and autoreactive Ig associated with malignancy, all of which arise from B cells expressing unconventional structural elements that may require transient escape from tolerance for successful expansion.